The effect of furazolidone on the growth of broilers and detection of its residues in tissues by hplc - Ahmet ACET; Behiç COŞKUN; Ömer DEMET; Bünyamin TRAŞ; Erol BAYTOK (Eurasian Journal of Veterinary Sciences)
Three experiments were conducted to examine the effect of furazolidone on the growth performance of broiler chickens and residue level and excrection time in edible meat, liver and kidney samples. In experiment 1, 240 day-old chicks were assigned to four groups with dietary treatmens including various levels (0, '5, 15, and 45 mg//kg feed) of furazolidone. The diets were fed to 4'2 days old and and growth performance of the groups were determined. In experiment 2, 45 chickens, 42 days old, in 3 groups were given furazolidone 0, 100, 200 mg/'kg feed iior 10 days. In experiment 3, two groups dhickens, each had 15 chickens, were feed furazolidone 300 and 500 mg/kg feed for 5 days as a curative dose. No benefical effects of dietary furazolidone on live weights but decreased feed intake.